Closed-loop speed control of switched reluctance motor drive fed from novel converter with reduced number of switches - Ashok Kumar Kolluru; Malligunta Kiran Kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents a novel converter configuration with fewer for switched reluctance motor (SRM) drive. The proposed novel converter insists for less number of switches compared to conventional asymmetrical type of converter configuration for switched reluctance motor. Switch count reduction in converter reduces the losses, volume of heat sink, and number of gate drive circuits and thereby the performance of the system. Closed loop speed control of switched reluctance motor fed from proposed novel converter topology was presented in this paper. Performance of closed loop operation is compared to open loop system. Further the proposed converter for SRMT is evaluated with loaded condition and comparative analysis of no-load and loaded SRM is presented. The model presented is developed and the results are analyzed using MATLAB/SIMULINK software. Closed loop performance of proposed novel converter fed switched reluctance motor drive is verified at fixed speed and variable speed conditions.